BrDDB1A maintains regular growth of Chinese cabbage via UV tolerance - Meidi Zhang; Jiaqi Zou; Shengnan Huang; Wei Fu; Yue Gao; Gaoyang Qu; Yonghui Zhao; Ying Zhao; Zhiyong Liu; Hui Feng (Vegetable Research)
Normal plant growth and development ensures the timely maturity and expected yield of crops. The repair mechanism of genome damage under adverse circumstances is essential for maintaining regular plant growth. Herein, two allelic growth retardation mutants of Chinese cabbage, grm1 and grm2, were obtained from EMS-mutagenized populations of wild-type 'FT' isolated-cultured microspores and seeds, respectively. Both mutants stably inherited and exhibited stunted growth with smaller leafy-heads. Genetic analysis and allelism test manifested that the mutated trait was triggered by a same single recessive nuclear gene. Via BSR-Seq, Brgrm1 was mapped to a target region including 20 genes on chromosome A09. Whole-genome re-sequencing revealed that BraA09g024830.3C in grm1 had a single base (A) deletion in the 17th exon, leading to a termination codon (TAG). Genotyping showed that the mutated phenotype co-segregated with the InDel in recombinants of the closest linkage markers. In addition, cloning of BraA09g024830.3C in grm2 found that a base substitution (G-A) occurred in the last base of the 1st intron causing an additional 263-bp retention in coding sequences, which in turn led to a termination codon (TAA). BraA09g024830.3C (BrDDB1A) is a homolog of Arabidopsis thaliana Damaged DNA Binding Protein 1A (DDB1A), a key gene of UV tolerance involved in DNA damage repair. The two mutants exhibited normal plant growth identical with wild-type under an extremely low UV radiation. Our results demonstrated that BrDDB1A contributes to maintaining regular plant growth in Chinese cabbage, which provide insights into elucidating the molecular mechanism underlying Chinese cabbage growth and development.